2017
DOI: 10.7243/2055-2386-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low level laser therapy versus pulsed electromagnetic field on diabetic peripheral neuropathy

Abstract: Background: Peripheral neuropathy is a common complaint of diabetes, leading to pain and reduced motor nerve conduction velocity. Clinical symptoms of peripheral neuropathy are present in approximately 25% of diabetic individuals, while nearly all diabetics have a reduction of nerve conduction velocity. Purpose: This study aimed to evaluate and compare the effect of low-level laser therapy (LLLT) versus pulsed electromagnetic field (PEMF) on pain intensity and motor nerve conduction velocity (MNCV) in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…[42] One study showed that the combination of TENS with oral pregabalin reduced VAS scores, persistent pain intensity scores short-form McGill Pain Questionnaire total scores, and sleep interference, after 4 weeks. [23] The other RCT investigated the effect of TENS plus subcutaneous injection of cobalamin alone or with lidocaine. The results of this study showed improvement in pain intensity mean allodynia, paresthesia scores, and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[42] One study showed that the combination of TENS with oral pregabalin reduced VAS scores, persistent pain intensity scores short-form McGill Pain Questionnaire total scores, and sleep interference, after 4 weeks. [23] The other RCT investigated the effect of TENS plus subcutaneous injection of cobalamin alone or with lidocaine. The results of this study showed improvement in pain intensity mean allodynia, paresthesia scores, and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…A-b afferents activity limits the transmission of information related to pain through the spinal cord and brainstem. [19] Previous studies proved the role of TENS for the treatment of PHN, [23][24][25] although there are numerous studies investigated the effect of PEMFS on different painful conditions, [11,[13][14][15][16][17] Due to the shortage of research to investigate the effect of PEMFS on PHN, specifically, according to PubMed database and Google scholar search, English language only, the current study is a novel randomized controlled trial -to the best knowledge of the authors-to investigate the effect of PEMFS on PHN in comparison to the pre-investigated TENS application.…”
Section: -Ref-cr6]mentioning
confidence: 99%
See 1 more Smart Citation